The influence of fouling on the dynamic behavior of PID-controlled heat exchangers. (25th October 2016) - Trafczynski, M.; Markowski, M.; Alabrudzinski, S.; Urbaniec, K.
Highlights: Heat recovery in industrial heat exchanger networks (HENs) saves energy. Dynamic behavior of PID-controlled heat exchangers can affect HEN performance. Dynamic model of a shell and tube heat exchanger is implemented in Simulink-Matlab. Effects of time-dependent fouling on the dynamics of heat exchangers are simulated. Adverse effects of fouling can be prevented by the tuning of PID controllers. Abstract: The influence of fouling build-up on the dynamic behavior of PID-controlled shell-and-tube heat exchangers was studied. A mathematical model was proposed in which heat exchanger is considered as an array of cells where the exchange of heat is modelled using lumped-parameter approach. The model was implemented employing Simulink/MATLAB software and validated using real-life data records acquired during 3 years of operation of a heat exchanger network coupled with a crude distillation unit. Using the validated dynamic model, a simulation study was carried out on selected PID-controlled exchangers operated in the mentioned network. For different periods of uninterrupted exchanger operation, that is, at different values of the thermal resistance of fouling, suitable controller tuning parameters were studied. The results proved that at changed thermal resistance of fouling, the values of tuning parameters should be changed too.